Prostate resected weight and postoperative prostate cancer incidence after transurethral resection of the prostate: A population-based study. Issue 3 (January 2019) - Liu, Fu-Chao; Hua, Kuo-Chun; Lin, Jr-Rung; Pang, See-Tong; Yu, Huang-Ping
Abstract : Abstract: To analyze whether different volumes of tissue resected during transurethral resection of the prostate (TURP) would associate with the subsequent development of prostate cancer. This population-based retrospective cohort study recruited 49, 206 patients with benign prostate hyperplasia (BPH) undergoing TURP between 2005 and 2012. Patients were recruited from the Taiwan National Health Insurance Research Database. Patients were separated into three groups, based on different volumes of tissue resected during TURP (5–15 g, 15–50 g, >50 g). Of the 49, 206 patients, 633 patients were diagnosed with new onset of prostate cancer following TURP. Older age was a risk factor contributing to the onset of prostate cancer ( P = .0196) and different volumes of tissue resected were significantly related to the incidence of postoperative prostate cancer ( P = .0399). The group of patients with a smaller volume of prostate resected had a higher risk of prostate cancer with a hazard ratio (HR) of 1.221 (95% confidence interval [CI]: 1.035, 1.440; P = .0179). However, the risk in the group of patients with a larger volume of prostrate resected was not significantly different, with an HR of 1.277 (95% CI: 0.981, 1662; P = .0690). The incidence of prostate cancer in Taiwanese males over 30 years of age has previously been reported to be 0.0560%; the mean incidence was 0.2282% in our present study. This study shows that BPH patients who had a smaller volume of tissue resected during TURP show a higher incidence of prostate cancer postoperatively. Currently, no clear mechanism is shown to demonstrate the relationship between resected prostate weight and the incidence of tumors. Patients with a larger prostate volume might have lower urinary tract symptoms earlier and then seek professional help. It is possible that surgical procedures might remove the potentially carcinogenic prostate tissue and thus reduce the risk of an aggressive tumor developing in the future.